2020
DOI: 10.1111/echo.14842
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cardiac structure and function between female powerlifters, fitness‐oriented athletes, and sedentary controls

Abstract: Aim: To compare echocardiographic parameters between female powerlifters, fitness-oriented athletes, and sedentary controls. Methods: A between-subject, cross-sectional experimental design was adopted. Echocardiographic parameters were measured in female powerlifters (n = 10; progressive overload 60%-95% of 1 repetition maximum [RM]), fitness-oriented athletes (n = 10; 50%-70% of 1-RM), and sedentary control subjects (n = 10). Comparisons were made with Kruskal-Wallis tests, one-way analyses of variance, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Participants were predominately male (n=1,733) with females representing 16% of participants (n=269). Six studies reported mixed groups including males and females, whilst two studies used only female participants [20,21]. The 32 studies presented in this review provided data on 949 resistance-trained athletes and 1053 untrained individuals.…”
Section: Study and Sample Characteristicsmentioning
confidence: 99%
“…Participants were predominately male (n=1,733) with females representing 16% of participants (n=269). Six studies reported mixed groups including males and females, whilst two studies used only female participants [20,21]. The 32 studies presented in this review provided data on 949 resistance-trained athletes and 1053 untrained individuals.…”
Section: Study and Sample Characteristicsmentioning
confidence: 99%
“…In this regard, an increased QTd has been documented in patients with arterial hypertension and left ventricular (LV) hypertrophy 7 . In addition to clinical environments, LV hypertrophy is observed in athletes completing regular training [8][9][10] . The LV hypertrophic cardiac response serves as a reactive mechanism to compensate for volume overload experienced during endurance training or pressure overload experienced during resistance training 11,12 .…”
mentioning
confidence: 99%